A structural mapping of mutations causing succinyl‐CoA:3‐ketoacid CoA transferase (SCOT) deficiency. Issue 6 (19th February 2013) - Shafqat, Naeem; Kavanagh, Kate L.; Sass, Jörn Oliver; Christensen, Ernst; Fukao, Toshiyuki; Lee, Wen Hwa; Oppermann, Udo; Yue, Wyatt W.
Abstract: Succinyl‐CoA:3‐ketoacid CoA transferase (SCOT) deficiency is a rare inherited metabolic disorder of ketone metabolism, characterized by ketoacidotic episodes and often permanent ketosis. To date there are ∼20 disease‐associated alleles on the OXCT1 gene that encodes the mitochondrial enzyme SCOT. SCOT catalyzes the first, rate‐limiting step of ketone body utilization in peripheral tissues, by transferring a CoA moiety from succinyl‐CoA to form acetoacetyl‐CoA, for entry into the tricarboxylic acid cycle for energy production. We have determined the crystal structure of human SCOT, providing a molecular understanding of the reported mutations based on their potential structural effects. An interactive version of this manuscript (which may contain additional mutations appended after acceptance of this manuscript) may be found on the web address:http://www.thesgc.org/jimd/SCOT .